The governess as a Gothic heroine in Henry James’ The turn of the screw - Gencheva, Andrea (English Studies at NBU, 2015)
One of the questions perpetually plaguing the critics of Henry James’ The Turn of the Screw is whether the ghosts are real or the governess had lost her mind. This paper offers an interpretation of James’ novella from the viewpoint of the Gothic novel, and the author draws parallels between the actions and behavior of the young and impressionable governess and those of a heroine from the Gothic genre, taking into account the governess’ narrative style, her repressed self, the evil she faces and finally, the overall position of governesses in Victorian society. The result is an aligning of James’ protagonist with the generally accepted image of a Gothic heroine, thus working towards the conclusion that, seen from the perspective of the Gothic novel, the ghosts are real and the governess is caught in a battle between good and evil, fighting for the children’s souls.